The Dynamics of Iran`s Chicken Meat Export Patterns in the Middle East Region - Mirzaei, F.; Yazdani, S.; Mostafavi, S.M. (International Journal of Poultry Science, 2005)
This study was conducted to determine the comparative advantage of Iran`s chicken meat export in the Middle East market. Trade and production policies and economic behaviour of producers and exporters have been in such a way that they could not show an appropriate and timely response of region, also the instabilities in the trends of RCA and RSCA indices during the study period (1993-2002) led to the conclusion that there is no well defined strategy and plan for utilization of low price production factors, effective human power, knowledge of bargaining power and target markets. Also regarding to poultry industry potential, we can`t recommend that Iran because of fluctuable RCA and RSCA indices, must retreat from recent decade of production policies for chicken meat production.